Formulating a legal framework for the protection of medical apologies in civil dispute resolution process - Jahn Kassim, Puteri Nemie; Mohamed, Duryana; Saleh, Muhammad Ridhwan (2019)
The role of apology in resolving conflicts and preventing litigation has gained much prominence. Particularly, in civil litigation, apology has the potential to promote negotiations, generate settlements, mitigate and absolve liability as it can be used as an effective tool at various stages during the civil dispute resolution process. For civil disputes involving medical practitioners and patients, apologies have the ability to defuse the spur of litigation and restore the relationship of trust and confidence between them. This is because apologies give recognition to the error that has occurred and reflect a sincere sense of remorse by the medical practitioner for causing the harm. Nevertheless, medical practitioners fear that apologies made will be interpreted as an admission of guilt and consequently, increases the possibilities of lawsuits causing negative effects on their medical indemnity coverage. In order to promote open disclosure standards amongst medical practitioners, several countries around the globe have enacted ‘Apology Laws’ which mandates the disclosure of medical errors under specific circumstances, while at the same time offering legal protection to those making the apologies. This research examines the possibilities of developing a legislative framework in Malaysia for the protection of apologies made by medical practitioners with the objective of safeguarding the benefits of apologies in promoting early settlements and reducing the number of litigated cases. Qualitative methods of research which include content analysis, random and structured interviews during field study will be employed to obtain the research output. The recommendations from this research will be a material source of reference for the Malaysian government to develop comprehensive ‘Apology Laws’ which will eventually reduce the number of potential lawsuits, promoting prospects of settlement and inculcate a sustainable culture of honesty and openness that is fundamental in gaining public trust within the healthcare system.